Lightweight coordination model for mobile collaborative mapping. (24th February 2021) - Mechaoui, Moulay Driss; Imine, Abdessamad
The rapid development of mobile devices features offers new opportunities for mobile peer-to-peer computing that can be used for providing location-based services and social/collaborative platforms using short-range networks. We are interested in collaborative mappings which provide computer support for nomadic users to manipulate at will and simultaneously a shared map on mobile devices. However, maintaining data consistency in mobile environment remains a challenging issue due to the arbitrary order of updates reception and the battery-life management. We propose a low-cost and flexible mobile collaborative mapping using simple primitive updates and easily customisable for rich features-based maps. No central coordination is necessary for preserving the shared map consistency. Indeed, we design a concurrency control protocol based on operational transformation (OT) approach to synchronise collaborative works in fully decentralised way. With a straightforward deployment on P2P networks, our application supports dynamic groups where mobile users can participate in and quit freely.